Engineering of Fc Multimers as a Protein Therapy for Autoimmune Disease - Fitzpatrick, Elizabeth A.; Wang, Jin; Strome, S. E. (Frontiers in Immunology, 2020)
The success of Intravenous Immunoglobulin in treating autoimmune and inflammatory processes such as immune thrombocytopenia purpura and Kawasaki disease has led to renewed interest in developing recombinant molecules capable of recapitulating these therapeutic effects. The anti-inflammatory properties of IVIG are, in part, due to the Fc region of the IgG molecule, which interacts with activating or inhibitory Fcγ receptors (FcγRs), the neonatal Fc Receptor, non-canonical FcRs expressed by immune cells and complement proteins. In most cases, Fc interactions with these cognate receptors are dependent upon avidity – avidity which naturally occurs when polyclonal antibodies recognize unique antigens on a given target. The functional consequences of these avid interactions include antibody dependent cell-mediated cytotoxicity, antibody dependent cell phagocytosis, degranulation, direct killing and / or complement activation – all of which are associated with long-term immunomodulatory effects. Many of these immunologic effects can be recapitulated using recombinant or non-recombinant approaches to induce Fc multimerization, affording the potential to develop a new class of therapeutics. In this review, we discuss the history of tolerance induction by immune complexes that has led to the therapeutic development of artificial Fc bearing immune aggregates and recombinant Fc multimers. The contribution of structure, aggregation and N-glycosylation to human IgG: FcγR interactions and the functional effect(s) of these interactions are reviewed. Understanding the mechanisms by which Fc multimers induce tolerance and attempts to engineer Fc multimers to target specific FcγRs and / or specific effector functions in autoimmune disorders is explored in detail.